Impact of cage aquaculture on water exchange in Sansha Bay. (15th October 2019) - Lin, Hongyang; Chen, Zhaozhang; Hu, Jianyu; Cucco, Andrea; Sun, Zhenyu; Chen, Xirong; Huang, Lingfeng
Abstract: Influence of cage aquaculture on the flow field and water exchange in Sansha Bay is investigated based on in situ current measurements and output from a two-dimensional shallow water hydrodynamic finite element model (SHYFEM). Without cage influence, the flow is relatively uniform in the vertical except a bottom Ekman layer. An asymmetry of tidal current speed is also observed in Sansha Bay with a dominance of the ebb tide. Near-surface current speed squared in cage-free area is typically larger than that within cage area by a factor exceeding three in deep channels, and by a factor of two in tidal flats. Current speed profiles suggest that cage-induced drag on the flow field can reach as deep as 20 m in the relatively deep channels of Sansha Bay. A set of numerical experiments are designed to quantify the relative effect of cages in tidal flats and channels, respectively, on water exchange using SHYFEM. It is shown that cage aquaculture weakens the local flow but seems to strengthen the flow adjacent to cages. Reducing the frictional drag in channels significantly increases the water exchange rate both locally and in the near-field tidal flats. Therefore, certain clearance or rearrangement of cage aquaculture in channels would be more effective in improving the water exchange in the entire Sansha Bay. Highlights: In Sansha Bay, near-surface current speed squared in cage-free area is typically larger than that within cage area by a factor exceeding three in deep channels, and by a factor of two in tidal flats. Cage aquaculture weakens the local flow but seems to strengthen the flow adjacent to cages. Certain clearance or rearrangement of cage aquaculture in channels would be more effective in improving the water exchange in the entire Sansha Bay.